The Auchi Kingdom: A century of growth and innovations 1920 - 2020: The achievements of the Auchi Kingdom in the last 100 years - Yakubu, Suleiman; Obomeghei, Wajeed (IJRDO - Journal of Social Science and Humanities Research, 2021)
The history of the Auchi Kingdom is one that has been given very little attention over the years despite the importance and significance of its robust and significant cultural heritage. The strategic location of the Kingdom was the reason why the British made it the headquarters of the former Kukuruku District by the British colonialist which later became defunct and renamed Afenmai in 1954. Despite the Kukuruku District became defunct, the Auchi Kingdom remained the Headquarters of Afenmai land. The Auchi Kingdom, as the Divisional Headquarters since 1920, attracted a lot of visitors and traders from far and wide who came for economic activities and also to witness the splendour of the ever growing and prosperous Kingdom. The Auchi Kingdom had experienced a lot of innovations, growth and development since the British established her rule over the Kingdom. Some notable innovations by the British colonialist includes new administrative policies, modern official staff building complex and quarters, new prison yard, Western Education, new network of roads, abolition of some bad cultural practices et.c. The end of British colonialism in 1960 did not put an end to the development in the Auchi Kingdom but surprisingly, it even increased till date. Auchi remains one of the fastest growing urban centers in Nigeria. The aim of this paper, therefore, is to celebrate a hundred years of a Kingdom as an administrative headquarters and to prove that the Kingdom had experienced progressive growth and innovations with physical evidence to show. This paper adopts a historical approach, with the use of primary and secondary sources, to arrive at its conclusion.